Farmakoterapija shizofrenije - Bačar, Cvetka (Farmacevtski vestnik, 2015)
Schizophrenia is a chronic mental disease that affects not only the patient but also his/her family, friends and his/her surroundings. First in line for the treatment of schizophrenia are antipsychotics which do not cure the illness but just reduce the psychotic symptoms and, consequently, improve the better quality of life of patients with schizophrenia. Since the use of antipsychotics not only bring benefits but also some risks for the patient, it is important the individual approach in selecting antipsychotic, dose and implementing treatment. Factors that decide the outcome of the treatment of schizophrenia are: (1) early recognition of the disease, (2) immediate treatment with antipsychotics, (3) the choice of the method and place of treatment, (4) the choice of appropriate antipsychotic, (5) compliance with the recommendations for the treatment of schizophrenia, (6) monitoring and recording the effects of antipsychotics, (7) team approach, and (8) the active involvement of the patient in the treatment process.
Keywords: shizofrenija; therapy; zdravljenje; antipsihotiki; individualni pristop